Digital Tulips? Returns to investors in initial coin offerings - Benedetti, Hugo; Kostovetsky, Leonard (Journal of Corporate Finance, 2021)
We analyze a dataset of 2390 completed ICOs, which raised a total of $12 billion in capital, nearly all since January 2017. We find evidence of significant ICO underpricing, with average returns of 179% from the ICO price to the first day's opening market price, over a holding period that averages just 16 days. After trading begins, tokens continue to appreciate in price, generating average buy-and-hold abnormal returns of 48% in the first 30 trading days. We also study the determinants of ICO underpricing and relate cryptocurrency prices to Twitter activity.